„Tecum per Romam ambulabamus”. Lekcje łaciny w esejach Micińskiego, Herberta, Krawczuka i Axera - Szczot, Monika (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2023)
The article has a complex structure. It begins with a brief overview of the teaching of Latin and its role in education. The main part of the article consists of analyses of essays containing descriptions of Latin lessons. The authors of the essays describe teachers and students, contrast past and present, talk about personal experiences, and show the role of Latin in contemporary culture. Latin not only described antiquity and the achievements of classical culture, but also formed the Polish language through its centuries–long presence in teaching systems. Krawczuk and Axer suggest that Latin improved morally, developed cognitively, and helped to better understand ancient literature and culture. Miciński and Herbert find in Latin lessons a moral signpost, humanism and a remedy for the totalitarianisms of the 20th century.